2021
DOI: 10.2147/cmar.s275096
|View full text |Cite
|
Sign up to set email alerts
|

LINC00665 Stimulates Breast Cancer Progression via Regulating miR-551b-5p

Abstract: Introduction Long intergenic non-protein coding RNA 665 (LINC00665) has been revealed to contribute cancer progression in many cancer types including liver and gastric cancer. However, the roles of LINC00665 in breast cancer (BC) remain to be explored. Methods We explored LINC00665 expression in BC tissues and normal tissues at GEPIA. Then, its expression in BC cells (HCC-1937, MDA-MB-231, and MCF-7) and normal cells (MCF10A) was analyzed with qRT-PCR. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…miR-551b-3p, expression level was also significantly downregulated in the gastric cancer tissues, which correlated with the degree of differentiation (i.e., tumor grade), TNM stage, and lymph node metastasis [ 56 ]. Downregulation of miR-551b-5p was reported in breast cancer cell lines and tissues and was an indicator of poor overall survival [ 57 ]. We observed downregulation of both miRs in PAC-resistant cell lines while in others during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…miR-551b-3p, expression level was also significantly downregulated in the gastric cancer tissues, which correlated with the degree of differentiation (i.e., tumor grade), TNM stage, and lymph node metastasis [ 56 ]. Downregulation of miR-551b-5p was reported in breast cancer cell lines and tissues and was an indicator of poor overall survival [ 57 ]. We observed downregulation of both miRs in PAC-resistant cell lines while in others during tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, knockdown of LINC00665 significantly inhibits the growth of breast cancer cells in vitro , significantly weakens the migration and invasion abilities, reduces the expression of EMT-related genes, and promotes apoptosis. By contrast, the overexpression of LINC00665 can promotes breast cancer progression ( 11 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LINC00665 expression was significantly associated with the tumor size and TNM stage, but not with the age of the breast cancer patients ( Lv et al, 2020 ). In addition, Qi et al conducted the Kaplan-Meier survival analysis to explore the correlation between LINC00665 expression and the prognosis of breast cancer patients ( Qi et al, 2021 ). They found that high expression of LINC00665 could predict poor overall survival of breast cancer patients ( Qi et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“…In addition, Qi et al conducted the Kaplan-Meier survival analysis to explore the correlation between LINC00665 expression and the prognosis of breast cancer patients ( Qi et al, 2021 ). They found that high expression of LINC00665 could predict poor overall survival of breast cancer patients ( Qi et al, 2021 ). Studies have reported that LINC00665 played a vital role in breast cancer progression, and LINC00665 Knockdown inhibited breast cancer cells proliferation, migration, and invasion but promoted apoptosis ( Ji et al, 2020 ; Lv et al, 2020 ; Zhou et al, 2020 ; Qi et al, 2021 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
See 1 more Smart Citation